2018
DOI: 10.1037/cou0000268
|View full text |Cite
|
Sign up to set email alerts
|

Cultural humility: Pilot study testing the social bonds hypothesis in interethnic couples.

Abstract: The purpose of this study was to explore factors associated with relationship quality in interethnic couples. Specifically, we tested the social bond hypotheses of humility in a sample of 155 individual participants currently in an interethnic relationship. Using a cross-sectional design, participants completed an online survey that included measures of demographics, conflict in their relationship, cultural humility, and relationship quality. We predicted that perceptions of one's partner's cultural humility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
12
0
2
Order By: Relevance
“…Likert-type scale ranging from 1 = strongly disagree to 5 = strongly agree , with higher scores indicating more self-perceived cultural humility (negative cultural humility items are reverse coded). The scale was modified to assess cultural humility towards LGBT individuals by prompting each item with, “Regarding LGBT individuals, I …” An example item is, “… I am open-minded.” This scale has previously shown internal consistency, with Cronbach’s alphas ranging from .86 to .93 in a variety of samples (Hook et al, 2013; McElroy, 2018). Both subscales were found to be internally consistent with the current sample with Cronbach’s alphas of .89 for positive cultural humility and .72 for negative cultural humility.…”
Section: Methodsmentioning
confidence: 99%
“…Likert-type scale ranging from 1 = strongly disagree to 5 = strongly agree , with higher scores indicating more self-perceived cultural humility (negative cultural humility items are reverse coded). The scale was modified to assess cultural humility towards LGBT individuals by prompting each item with, “Regarding LGBT individuals, I …” An example item is, “… I am open-minded.” This scale has previously shown internal consistency, with Cronbach’s alphas ranging from .86 to .93 in a variety of samples (Hook et al, 2013; McElroy, 2018). Both subscales were found to be internally consistent with the current sample with Cronbach’s alphas of .89 for positive cultural humility and .72 for negative cultural humility.…”
Section: Methodsmentioning
confidence: 99%
“…We predicted that collective self-esteem (both public and private), disability adjustment, anxious attachment, and avoidant attachment would serve as correlates and unique predictors of dyadic adjustment, commitment, and dyadic trust for those who identified as sexual minority persons with disabilities. Additionally, we aimed to test the social bond hypothesis (McElroy-Heltzel et al, 2018), by examining if perceptions of partner's cultural humility toward disability would serve as a significant correlate and unique predictor of dyadic adjustment, commitment, and dyadic trust for sexual minority persons with disabilities.…”
Section: Purpose Of the Present Studymentioning
confidence: 99%
“…One study found that perceptions of a spouse’s cultural humility was related to relationship satisfaction (Wang, Rankin, & Chong, 2015). Another study found that ineffective arguing caused individuals in interethnic relationships to rate their partners lower on cultural humility, which in turn decreased relationship satisfaction and commitment (McElroy-Heltzel et al, 2018). More broadly, humility has been associated with forgiveness (Davis et al, 2013), commitment, and relationship satisfaction (Farrell et al, 2015) in romantic relationships.…”
Section: The Social Bonds Hypothesis Of Humilitymentioning
confidence: 99%
“…Они в большей степени, чем женщины из монокультурных семей, стремятся к эмоциональной близости со своим партне-ром, испытывают меньше фрустрации в романтических отношениях, у них отмечается меньше негативных и амбивалентных эмоций в отношениях, они меньше стремятся дистанцироваться либо эмоционально сливаться со своим партнером, устанавливая зависимые отношения, меньше его ревнуют. Помимо упомянутого выше предположения о личностных особенностях, связанных с готовностью создавать межкультурные браки, эти результаты можно объяснить межкультурными различиями в стилях привязанности (Agishtein, Brumbaugh, 2013) в сочетании с концепцией социальных связей (McElroy-Heltzel et al, 2018). То есть женщины из монокультурных браков в большей степени придерживаются своей культурной традиции построения отношений.…”
Section: стили привязанности к партнеру женщин состоящих в межкультурных и монокультурных бракахunclassified
“…В работах McElroy-Heltzel с соавторами гипотеза социальных связей применяется для объяснения приверженности отношениям и удовлетворенности отношениями в межкультурных парах. Согласно этим данным, имеется связь воспринимаемой каждым из супругов степени их приспособления к культуре друг друга и качеством отношений в паре, в том числе проявляющимся в снижении неконструктивных конфликтов на основе культурных различий (McElroy-Heltzel et al, 2018).…”
Section: Introductionunclassified